Catalytic function of CeO2 in non-reductive conversion of CO2 with alcohols. (September 2020) - Tomishige, K.; Gu, Y.; Chang, T.; Tamura, M.; Nakagawa, Y.
Abstract: CeO2 shows unique catalytic properties by an acid–base bifunctionality as well as redox properties. The acid–base bifunctional properties of CeO2 have been applied to the non-reductive CO2 conversion with alcohols such as dimethyl carbonate (DMC) synthesis from CO2 and methanol. CeO2 shows very high selectivity to DMC; however, the yield of DMC is strongly limited by the equilibrium. The combination of the synthesis of organic carbonates from CO2 and corresponding alcohols with suitable H2 O removal methods can enhance the yield of the organic carbonates beyond the equilibrium limitation. Many CeO2 -based materials have been prepared and tested in the reaction of CO2 with alcohols. As is known, what catalysts can do is to make the reactions progress to the equilibrium level in reversible reactions and the catalysts do not influence the equilibrium level and thermodynamics of the reactions. In order to evaluate the catalytic properties of CeO2 -based materials in this reaction, we should pay more attention to the catalytic activity. In addition, the catalytic activity should be measured under the reaction conditions at a sufficiently lower conversion level than that at the equilibrium level, because the effect of the reverse reaction can be neglected. The catalytic performance of the CeO2 -based materials is compared considering the equilibrium level under the reaction conditions. Morphology, oxide ion defects (or oxygen vacancies), as well as acid–base properties on the catalytic performance can influence the catalytic activity; however, it seems to be difficult to elucidate crucial factors. Therefore, development of CeO2 -based materials with much higher catalytic activities than reported results is necessary, which will contribute to the determination of the most crucial factor. Graphical abstract: Image 1 Highlight: CeO2 is an effective material for the non-reductive conversion of CO2 with alcohols. Reaction of CO2 with alcohols over CeO2 -based materials gives corresponding organic carbonates with high selectivity. Reaction of CO2 with alcohols to corresponding organic carbonates is limited by the serious equilibrium. The combination of the reaction of CO2 with alcohols with suitable H2 O removal methods can enhance the yield of corresponding organic carbonates. Development of CeO2 -based materials with higher catalytic performance from the viewpoint of catalytic activity, stability, wider substrate scope, and so on is important.